Manuelzão’s feast - Maria da Gloria Bordini (Signo, 2017)
Guimarães Rosa’s short story “Uma estória de amor” can be interpreted as a philosophical consideration on existence and its finitude, and the workings of love, if compared with Plato’s Symposium, and his theory of the nature and quality of Eros. Several critics attest Rosa’s readings of Plato, and a comparative approach between both texts reveals the reflection of Plato’s ideas fictionalized in the course of Manuelzão’s feast, concurring to produce a moving account of the complexities and contradictions of love among simple people of Sertão.